2017
DOI: 10.1002/jsfa.8294
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Lactobacillus acidophilus surface‐layer protein and its immunomodulatory effects on RAW264.7 cells

Abstract: SLP can trigger immunomodulatory effects in RAW 264.7 cells. This provides crucial information that will enable the further use of L. acidophilus in food, medicine and other products. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…SLPs of probiotics also have many benefits to the host. Recent studies found that SLPs purified from Lactobacillus exerted immunomodulatory effects, which attenuated intestinal barrier dysfunction and inflammation, and protected intestinal epithelial barrier (Prado Acosta et al, 2016;Zhang et al, 2017;Wang et al, 2019). Surface-layer protein A (SlpA) is a S-layer protein specifically found in L. acidophilus NCFM.…”
Section: Surface-layers Proteinsmentioning
confidence: 99%
“…SLPs of probiotics also have many benefits to the host. Recent studies found that SLPs purified from Lactobacillus exerted immunomodulatory effects, which attenuated intestinal barrier dysfunction and inflammation, and protected intestinal epithelial barrier (Prado Acosta et al, 2016;Zhang et al, 2017;Wang et al, 2019). Surface-layer protein A (SlpA) is a S-layer protein specifically found in L. acidophilus NCFM.…”
Section: Surface-layers Proteinsmentioning
confidence: 99%
“…Our group has previously determined L. acidophilus CICC 6074 S-layer protein as an active ingredient of LAB and tested itscapabilities to regulate the immune system. ,, This research further investigated the underlying molecular mechanism of the S-layer protein on the cytotoxic function against colon cancer HT-29 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies indicated that the L. acidophilus CICC 6074 S-layer protein has intestinal adhesion and immune system regulation abilities. ,, As immunotherapy is considered as an underlying cancer treatment, we predict that the S-layer protein may have potential cytotoxic functions on colon cancer cells.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Gel filtration chromatography can separate small and large molecules from interfering matrices (Lian et al 2016 ). So, it is easy to isolate contaminants from high molecular weight interferences and widely used on the basis of the different molecular weights of proteins employed to separate the different components of a sample (Zhang et al 2017 ). The method can effectively purify the target protein, ensure the biological activity of the recombinant protein, and avoid the irreversible degeneration caused by too-long treatment of the denaturant.…”
Section: Discussionmentioning
confidence: 99%